Effects on Folsomia candida Willem, 1902 of products resulting from anaerobic digestion of biomass tested at different soil pH - Michele d’Errico; Marina Mauri; Rosa Taurino; Isabella Lancellotti; Maria Agnese Sabatini (Soil Organisms, 2015)
In recent years, it has become increasingly important to reduce the production and impact of wastes on the environment to save and restore natural resources. A way of disposing industrial, agro-industrial and urban wastes is their treatment by anaerobic digestion, with the production of biogas and residual organic material. The latter is commonly called digestate and can be used in agriculture as fertilizer, soil improver or adsorbent material, but only scarce or no evaluations of its biological effects on soil organisms are presently available. The aim of the present research was to study the effects of digestate, when added to soils with different pH values, on the survival and reproduction of the collembolan Folsomia candida. The digestate investigated in this study was obtained from agro-industrial wastes mixed with biological sludge. We exposed springtails to two different concentrations of digestate (2.5 %, 5 %) in two artificial soils with pH values of 6 and 4.5. The addition of digestate resulted in an increase of experimental-soil pH values, depending on the concentration and original pH value of the artificial soil used. The negative effects of digestate detected on the survival and reproduction of F. candida was mainly attributed to pH values > 6. The high pH value, however, does not explain by itself the strong decrease in number of juveniles in the experimental soil when the highest concentration of digestate was combined with the highest pH value reached. In this case it is possible to assume a combined effect of pH and other digestate characteristics, such as nitrogen content and salinity, currently under study.